1996
DOI: 10.1046/j.1471-4159.1996.67041718.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Precursors and Compartmentation of Cerebral GABA in Vigabatrin‐Treated Rats

Abstract: The metabolic precursors and cerebral compartmentation of the augmented GABA pool induced by vigabatrin, an irreversible inhibitor of GABA transaminase, have been investigated by 13C NMR. Adult rats receiving rat chow ad libitum were given either drinking water only or drinking water containing 2.5 g/L vigabatrin for 7 days. Both groups of animals were infused either with [1,2‐13C2]acetate (15 µmol/min/100 g body weight), an exclusive precursor of GABA formation through the glial glutamine pathway, or with [1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 33 publications
(52 reference statements)
3
50
1
Order By: Relevance
“…Various ex vivo as well as in vitro NMR studies using different 13 C-labelled substrates provided concurrent evidence contradicting the neuronal localization of pyruvate 59,61,94,195 However, studies using 13 C-labelled acetate (with or without 13 Clabelled glucose) in animal models 59,65 and in primary astrocyte cultures 49,81 showed that up to 20% of lactate was derived from acetate after recycling of pyruvate. The total formation of brain lactate from TCA cycle intermediates was calculated as follows: 59 the percentage 13 Cenrichment in lactate C-2 and C-3 derived from [2-13 C 1 ]acetate was approximately 2%, and that of (whole brain) glutamate C-3 and C-4 was 2.6%.…”
Section: Pyruvate Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ex vivo as well as in vitro NMR studies using different 13 C-labelled substrates provided concurrent evidence contradicting the neuronal localization of pyruvate 59,61,94,195 However, studies using 13 C-labelled acetate (with or without 13 Clabelled glucose) in animal models 59,65 and in primary astrocyte cultures 49,81 showed that up to 20% of lactate was derived from acetate after recycling of pyruvate. The total formation of brain lactate from TCA cycle intermediates was calculated as follows: 59 the percentage 13 Cenrichment in lactate C-2 and C-3 derived from [2-13 C 1 ]acetate was approximately 2%, and that of (whole brain) glutamate C-3 and C-4 was 2.6%.…”
Section: Pyruvate Recyclingmentioning
confidence: 99%
“…Approximately 5 nmol/min/mg of the TCA cycle flux may be mediated by pyruvate recycling considering a relative flux of 30% 64 of the TCA cycle through pyruvate recycling and cerebral TCA cycle rates of approximately 15 nmol/ min per mg protein. 61,196,199 Comparison with maximal activities of ME and PEPCK in the brain (7.6 and 1.6 nmol/min/mg protein), 64 suggests that the capacity of these enzymes will be unlikely to limit the recycling rates in the brain in vivo. Furthermore, while the activities of ME and PEPCK are very low in neurons (approximately 0.3 nmol/min/mg protein and not detectable, respectively), they are much higher in astrocytes (approx.…”
mentioning
confidence: 99%
“…Peak assignments based on the previous reports (3,(23)(24)(25) were confirmed in in vivo spectra and in spectra from model solutions of NAA, glutamate, glutamine, phosphorylcholine (PC), creatine (Cr), phosphocreatine (PCr), myoinositol (mI), aspartate, lactate, alanine, and HCO 3 -, as described by Bluml et al (4). All spectra were processed off-line on a Sun SPARCstation 2 using the SA/GE software package provided by General Electric.…”
Section: Mrs Processingmentioning
confidence: 99%
“…13 C MRS, also developed 30 years ago, held the promise of circumventing many problems by offering dynamic metabolic analysis. 2,3 It is the purpose of this Review to examine the hypothesis that dynamic analysis of metabolite flux rates in vivo is more powerful in clinical investigation than static analysis. In other words, that 13 C NMR after enrichment provides more useful diagnostic information than other steady-state concentration measurements using 1 H, 31 P, 23 Na etc., and thereby compensates for its poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%